Ceļa atrašana labirintā - Gorbunovs, Ivans (Latvijas Universitāte, 2019)
Darbs demonstrē, kā var izmantot viļņu algoritmu ceļa atrašanai labirintā. Darbā tiek izpētīts viļņu algoritms, rezultātā ir izveidota lietotne, kurā ir realizēts viļņu algoritms un trīs tā modifikācijas. Salīdzinot modifikācijas, tiek secināts, ka 3. modifikācija ir visefektīvākā.

The present research paper deals with the investigation of wave algorithm for the solving of mazes. The paper aims to create a program that finds a path in the maze. Moreover, it aims to modify wave algorithm and to compare the wave algorithm and the productivity of its modifications. The author of the paper developed the program for maze solving. Moreover, the wave algorithm and its modifications were implemented. The study has shown that third modification was the most effective.
Finding a path in a maze
Keywords: Datorzinātne; viļņu algoritms; labirints; grafs; grafu teorija